Comparative effectiveness of treatment options for plantar heel pain: a systematic review with network meta-analysis. Issue 3 (28th June 2018) - Babatunde, Opeyemi O; Legha, Amardeep; Littlewood, Chris; Chesterton, Linda S; Thomas, Martin J; Menz, Hylton B; van der Windt, Danielle; Roddy, Edward
Abstract : Objective: To evaluate the comparative effectiveness of current treatment options for plantar heel pain (PHP). Design: Systematic review and network meta-analysis (NMA). Data sources: Medline, EMBASE, CINAHL, AMED, PEDro, Cochrane Database, Web of Science and WHO Clinical Trials Platform were searched from their inception until January 2018. Study selection: Randomised controlled trials (RCTs) of adults with PHP investigating common treatments (ie, corticosteroid injection, non-steroidal anti-inflammatory drugs, therapeutic exercise, orthoses and/or extracorporeal shockwave therapy (ESWT)) compared with each other or a no treatment, placebo/sham control. Data extraction and analysis: Data were extracted and checked for accuracy and completeness by pairs of reviewers. Primary outcomes were pain and function. Comparative treatment effects were analysed by random effects NMA in the short term, medium term and long term. Relative ranking of treatments was assessed by surface under the cumulative ranking probabilities (0–100 scale). Results: Thirty-one RCTs (total n=2450 patients) were included. There was no evidence of inconsistency detected between direct and indirect treatment comparisons in the networks, but sparse data led to frequently wide CIs. Available evidence does not suggest that any of the commonly used treatments for the management of PHP are better than any other, although corticosteroid injections, alone or in combination with exercise, and ESWT were ranked most likely to be effective for the management of short-term, medium-term and long-term pain or function; placebo/sham/control appeared least likely to be effective; and exercise appeared to only be beneficial for long-term pain or function. Conclusions: Current evidence is equivocal regarding which treatment is the most effective for the management of PHP. Given limited understanding of long-term effects, there is need for large, methodologically robust multicentre RCTs investigating and directly comparing commonly used treatments for the management of PHP. PROSPERO registration number: CRD42016046963.